2022
DOI: 10.12669/pjms.38.5.5749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Montelukast sodium combined with Budesonide aerosol on airway function and T lymphocytes in asthmatic children

Abstract: Objectives: To investigate the effects of Montelukast sodium combined with Budesonide aerosol on airway function and T lymphocytes in asthmatic children. Methods: The records of 86 pediatric asthma patients, treated in Huzhou Maternal and Child Health Hospital from February 2020 to March 2021, were studied retrospectively. Of them, 40 children received routine treatment + budesonide atomizer (Group-I), and 46 patients received routine treatment + budesonide atomizer + montelukast sodium (Group-II). The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…1, the LAT values of the control group before and after treatment were (45.21±6.09 and 25.34±4.12) and the ODI 4 % values were (25.63±5. 19 Before treatment, there was no significant difference in LAT, ODI 4 % and AHI levels between the two groups (p>0.05). After treatment, the LAT, ODI 4 % and AHI levels of the observation group were significantly lower than those of the control group (p<0.05).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…1, the LAT values of the control group before and after treatment were (45.21±6.09 and 25.34±4.12) and the ODI 4 % values were (25.63±5. 19 Before treatment, there was no significant difference in LAT, ODI 4 % and AHI levels between the two groups (p>0.05). After treatment, the LAT, ODI 4 % and AHI levels of the observation group were significantly lower than those of the control group (p<0.05).…”
Section: Resultsmentioning
confidence: 80%
“…Studies have shown that the combination of these two drugs can have a synergistic effect, further improving the treatment effectiveness for children. Surgical treatment is achieved by removing enlarged lesions in children to improve clinical symptoms [19] . The traditional surgical methods for pediatric snoring are tonsillectomy and adenoidectomy, and the traditional surgical treatment effective rate can reach 85 % to 90 % [20] .…”
Section: Basic Data Informationmentioning
confidence: 99%
“…Montelukast sodium belongs to a type of leukotriene antagonist that is selective. [7][8][9] It can prevent leukotriene from attaching to receptors, thus regulating inflammation while compensating for budesonide's limitations. [10][11][12] Therefore, to further investigate the clinical therapeutic effect of budesonide combined with montelukast sodium in bronchial asthma, 86 children with bronchial asthma admitted to our hospital from January 2019 to December 2020 were selected for the following study and report.…”
Section: Introductionmentioning
confidence: 99%